Deep Brain Stimulation for Refractory Temporal Lobe Epilepsy. Current Status and Future Trends - Velasco, Francisco; Saucedo-Alvarado, Pablo E.; Vazquez-Barron, Daruny; Trejo, David; Velasco, Ana Luisa (Frontiers in Neurology, 2022)
A comparative analysis of the targets for deep brain stimulation (DBS) to treat refractory temporal lobe epilepsy and the rationale for its use is presented, with an emphasis on the latency to obtain significant antiepileptic effect and long term seizure control. The analysis includes consideration of surgical techniques currently used to optimize antiseizure effects and decrease surgical risks. Seizure control is similar to programmed DBS and DBS responsive to abnormal cortical or subcortical EEG activity. There is no difference in the long-term seizure control between programmed and responsive and intermittent or continuous DBS, although, intermittent programmed DBS may have a significant antiseizure effect starting in the first month when applied to non-sclerotic tissue, such as the parahippocampal cortex. There is no neuropsychological deterioration induced by DBS.